Safety of active catheters in MRI: Termination impedance versus RF‐induced heating. Issue 2 (22nd October 2018) - Özen, Ali Caglar; Lottner, Thomas; Bock, Michael
Abstract : Purpose: To investigate the effect of the termination impedance on the RF‐induced heating of active catheters using analytical modeling. Theory and Methods: Interaction of an arbitrary electric (E) field and an isolated transmission line (TL) embedded in cascaded lossy media was analytically modeled. Termination impedances at the tip and the input sides were expressed as distinct parameters in the current and voltage distribution formulae that are obtained by solving the inhomogeneous wave equations using the Green's function approach. The tip specific absorption rate (SAR) was calculated for different E field configurations. The tip SAR was displayed on a color‐coded Smith chart in terms of the normalized input reflection coefficient. Results of the analytical calculations were compared to transfer function (TF) measurements. An input impedance control unit that is integrated to the interface circuit was introduced. Results: TFs from analytical model and measurements exhibited similar behaviors. Color‐coded Smith charts shows that the analytical model and measured TF‐based tip SAR depends strongly on the input reflection coefficient. Both for measured and analytical TFs, SAR can deviate up to 70% from the mean value for different input impedance values. Conclusion: This study shows that it is possible to change the RF‐induced heating characteristics of an active catheter by adjusting the input impedance, and the presented analytical model is in good agreement with TF measurements.